(untitled) (UNIZIK Journal of Marketing, 2025)
This study was carried out to establish how service providers in the hospitality industry, which is highly characterized by service homogeneity and intense competition, can gain competitive advantage over rivals through the practice of excellent customer service. The theoretical framework adopted for the study was the Service-Dominant (S- D) logic theory. The study established that unlike products, which because of advances in technology, have assumed commodity status, it is not so with customer service, which is largely intangible and therefore difficult to imitate; implying that service differentiation based on it is a sure bet in gaining competitive advantage over rivals in the hospitality industry. Having established that excellent customer service influences customer perception in the industry and that “your perception by your customers is your reality”, the paper identified customer expectations in the industry and made specific recommendations on the customer service measures to take when interacting with customers; with being available, friendly, respectful, helpful and attentive as well as not only meeting but exceeding customer expectations by ensuring that value promised is value delivered as essentials. When this is the case, the resultant benefits would include but not limited to: repeat patronage, thus harvesting from the customer’s life –time value (CLV) , positive word-of-mouth (W.O.M) from satisfied customers, which encourages trial patronage from new customers and excellent reviews in the social media which are conditions necessary for the sustenance of operations, growth and profitability. As poor customer service has been credited with accounting for about 68% of the reasons why customers defect, to gain competitive advantage in the hospitality industry, a strong culture of customer service excellence should as a matter of necessity be adopted by hospitality services providers.